Phytoplankton from natural water bodies of the Patagonian Plateau - Izaguirre, Irina (2014)
The Patagonian Plateau is one of the most arid regions of Argentina, where mean annual rainfall ranges between 100 and 200 mm. This region contains different types of water bodies: large artificial lakes, permanent natural lakes, rivers and temporary ponds. In comparison with the Andean lakes, the available information on phytoplankton from the natural water bodies of the steppe is scarcer. In general, most lakes in this region range from mesotrophic to eutrophic. Limnological regional studies have shown that nutrient concentrations and algal biomass of the lakes located in the ecotone zone (pre-Andean) and in the Patagonian Plateau are higher compared with those registered in the Andean lakes. The dominant algal groups in most of the surveyed water bodies of the steppe are usually Chlorophyceae, Bacillariophyceae and Cryptophyceae. Cyanobacteria seem to be more abundant in some lakes of the steppe with fish introduction.